Comparison of spinal analgesia with Lidocaine plus Buprenorphine and Lidocaine alone - M Rabiei (Babol University of Medical Sciences, 2004)
Background and Objective: The control of postoperative pain that is one of the main goals of anesthesia care can lead to patients’ satisfaction and reduce time and expense of hospitalization. This study was done to compare the postoperative analgesia indices of free Lidocaine spinal anesthesia with Lidocaine plus Buprenorphine. Methods: This clinical trial study was performed on 100 patients aged 17-80 years in ASA Class I. They were randomly divided into two groups (Each group=50). In group 1 (Control), 75-100 mg Lidocaine (5%) with 0.5ml distilled water and in group 2 (Study), 75-100 mg Lidocaine (5%) plus 50µg Buprenorphine were injected intrathecally equal volumes. Patients were followed up for 24 hrs because of vital sign, severity of pain and respiratory rate and then compared to each other. Findings: The mean duration of postoperative analgesia in group 1 and 2 were 2.1 and 22.7 hours, respectively (P=0.000). The difference of range of hemodynamic changes was not statistically significant. Conclusion: According to the results, the mean duration of postoperative analgesia in study group (Buprenorphine+Lidocaine) was longer than the control group and there were no hemodynamic changes between two groups.